Development of Self-Directed Learning Readiness Scale for Vietnamese Undergraduates - Thuy, Dang Thi Thanh (VNU Journal of Science: Education Research, 2022)
This study aimed to develop a valid and reliable instrument to diagnose students’ attitudes, abilities and personality characteristics, necessary for self-directed learning among undergraduate students in Vietnam. The study was undergone into two stages including developing and testing the questionaire. Besides desk study, expert interview was utilized to 05 experts and 30 undergaraduate students in educational measurement to assess the content and construct validity of a number of items perceived to reflect self-directed learning readiness in the questionaire. At the same time, the software of SPSS 26.0 was utilized to ensure the validity and reliability of the scale after the testing stage with a sample 1200 students who are studying education science and natural science & technology . The research result showed that, Cronbach's alpha coefficients was above 0.8 and 42/42 questions have a total variable correlation of over 0.03, ensuring the reliability of the scale. That is expected to allow educators to assess and diagnose their students’ learning needs and their readiness for learning, thereby supporting the educators to implement teaching strategies that will best suit the students. Furthermore, the development of this scale will provide valuable data for curriculum development at the higher education institutions.